2018
DOI: 10.1126/science.aat0572
|View full text |Cite
|
Sign up to set email alerts
|

Defining the human C2H2 zinc finger degrome targeted by thalidomide analogs through CRBN

Abstract: The small molecules thalidomide, lenalidomide, and pomalidomide induce the ubiquitination and proteasomal degradation of the transcription factors Ikaros (IKZF1) and Aiolos (IKZF3) by recruiting a Cys2-His2 (C2H2) zinc finger domain to Cereblon (CRBN), the substrate receptor of the CRL4CRBN E3 ubiquitin ligase. Here we screened the human C2H2 zinc finger proteome for degradation in the presence of thalidomide analogs, identifying 11 zinc finger degrons. Structural and functional characterization of the C2H2 zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
496
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(504 citation statements)
references
References 41 publications
8
496
0
Order By: Relevance
“…The therapeutic potential of targeted protein degradation has been demonstrated by the success of thalidomide-related anti-cancer drugs (often referred to as immunomodulatory drugs, or IMiDs). IMiDs bind CRBN, the substrate receptor of the CUL4-RBX1-DDB1-CRBN (CRL4 CRBN ) E3 ubiquitin ligase 25 , and generate a novel binding surface to recruit and ubiquitinate neo -substrates 610 . Such molecular glues present an opportunity to target virtually any protein for degradation, even in the absence of a defined binding pocket.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic potential of targeted protein degradation has been demonstrated by the success of thalidomide-related anti-cancer drugs (often referred to as immunomodulatory drugs, or IMiDs). IMiDs bind CRBN, the substrate receptor of the CUL4-RBX1-DDB1-CRBN (CRL4 CRBN ) E3 ubiquitin ligase 25 , and generate a novel binding surface to recruit and ubiquitinate neo -substrates 610 . Such molecular glues present an opportunity to target virtually any protein for degradation, even in the absence of a defined binding pocket.…”
mentioning
confidence: 99%
“…However, novel genetic dependencies in acute myeloid leukemia (AML) suggest a potential for clinical development 16 , and a recent phase II study encourages development with appropriate biomarkers 17 . Moreover, the aryl-sulfonamides appear to promote binding of DCAF15 to the RNA recognition motif (RRM) of RBM39, which suggests that derivatives of the aryl-sulfonamides may be used to target other RRM-containing proteins 9,10 . However, a detailed picture of the mechanism by which sulfonamides engage CRL4 DCAF15 to promote turnover of the neo -substrate RBM39 is critically required to further leverage this new class of drugs for the targeting of RBM39, more generally of RRM containing proteins, and for the broad application of molecular glue degraders.…”
mentioning
confidence: 99%
“…In addition, we identified a number of zinc finger proteins, including WIZ. Note that while this work was being prepared for submission, Thomä and colleagues reported the interaction of a large collection of zinc fingers proteins with CRBN, including those reported here (44).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that manipulation of molecular glue scaffolds change neo-substrate scope. For example, thalidomide analogs still bind to cereblon but engage in glue interactions with different neosubstrates leading to their degradation 19 . Rapamycin analogs glue FKBP proteins to different neo-substrate proteins leading to modulation of their function 18,18,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, analogs of rapamycin and thalidomide can maintain their respective binding to their FKBP12 and cereblon targets but shift their neo-substrate binding profiles to confer new and distinct biological functions [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%